Digital Marketing dan Hedonisme Dalam Pengambilan Keputusan Pembelian - I Putu Lugra Agusta Pranawa; Agus Putu Abiyasa (Universitas Pendidikan Nasional, 2019)
ABSTRACTThis study discusses digital marketing strategies and hedonism on purchasing decisions. The research location was conducted at the Bali Tree House. The sampling technique uses purposive sampling technique, data collection techniques used are: observation, documentation, and interviews, with the validity method of triangulation data. The results found are as follows: Rumah Pohon Bali has used a digital marketing strategy using E-commerce, blogs, and social media for digital marketing optimization. Hedonism combined with digital marketing with visual summaries can increase consumer attractiveness. This digital marketing strategy and hedosme can increase purchasing decisions through policy factors and social factors regarding the part of the reference group that is expected to be a strategy that can provide maximum sales results for Balinese tree houses.